The Variety of Religiosities in Contemporary Turkey - Sarah Demmrich; Hasan Kaplan; Abdulkerim Şenel (European Journal of Turkish Studies)
The topic of religiosity in Turkey is often restricted to studies of secularization or fundamentalism. However, new religious phenomena, especially deism, are now drawing much attention in Turkey, yet most studies are focusing on small samples. Our study widens this view by presenting questionnaire data on a variety of religious self-assessment categories derived from a representative quota sample in relationship to sociodemographic and other religiosity variables. Only one-third define themselves as orthodox religious while 62 % identify as ‘believers’. The categories deism, non-belief/atheism, and religiously indecisiveness cover 7.2 % in total. Orthodox religious individuals differ in their sociodemographic profile from the rest (are older, more rural, less educated, higher rate of unemployment) and a sharp drop of all religiosity scores was observed from the orthodox religious to the rest. Deists, non-believers/atheists, and religiously indecisive individuals can, together with some ‘believers’, be grouped into a highly secularized cluster. Our findings suggest that there is a huge variety of religiosities in contemporary Turkey, despite the over-religionization imposed by the current government. Religious educators and clergy should welcome such changes by promoting development towards religious maturity independent of political agendas.